EFEITO DO Ca, B, Mo e Zn NA PRODUÇÃO DE MATÉRIA SECA DE SOJA (Glycine Max, L.) - Grassi Filho, Hélio; Lima, Leonia Apparecida de; Soares, Edmir; Casselli Júnior, Arnaldo; Pieri, José Carlos de (REVISTA DE AGRICULTURA, 2015)
EFEITO DO Ca, B, Mo e Zn NA PRODUÇÃO DE MATÉRIA SECA DE SOJA (Glycine Max, L.)